A preliminary content validity study of the Malay version of READI-SF - Affizal Ahmad,; Nik Nor Sumazeani Nik Min,; Mohd Normani Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Readiness for treatment reflects the individual’s motivation to seek help and preparedness to engage in treatment activities. The READI-SF aimed to assess parental readiness to engage in treatment. The present study aimed to translate the English version of READI-SF into the Malay language and subsequently assess its content validity using the content validity ratio (CVR), content validity index (CVI) and modified kappa analyses. Four independent translators carried out the translation procedures. Eight clinical professionals were involved as content experts. Of 17 items, six items needed to be revised due to low CVR values (< 0.75). Based on unfavourable individual CVI (I-CVI) results (< 0.78), two items (for item relevancy) and six items (for item clarity) had to be modified. The overall CVI of the questionnaire (S-CVI) was found to be good (i.e., 0.91 for item relevancy and 0.83 for item clarity). Nine items needed to be revised, and the modifications were carried out accordingly. At the end of the study, a valid Malay-translated READI-SF was produced. It has good potential to serve as a clinical tool to assess the readiness of Malay-speaking parents to engage in treatment. However, prior to its intended clinical application, further research is warranted to assess other aspects of validity (e.g., face validity, construct validity, and criterion-related validity), as well as READI-SF reliability.